Primary and managed care. Ingredients for health care reform. - Bindman, A B (1994)
The use of primary and managed care is likely to increase under proposed federal health care reform. I review the definition of primary care and primary care physicians and show that this delivery model can affect access to medical care, the cost of treatment, and the quality of services. Because the use of primary care is often greater in managed care than in fee-for-service, I compare the two insurance systems to further understand the delivery of primary care. Research suggests that primary care can help meet the goal of providing accessible, cost-effective, and high-quality care, but that changes in medical education and marketplace incentives will be needed to encourage students and trained physicians to enter this field.